THE FAILURE OF DESCENTRALIZATION IN ARGENTINA (Andamios, Revista de Investigación Social, 2007)
This paper has the objective of carrying out a critical analysis of the theories that justified the decentralizing process in the Republic of Argentina, trying to determine, from the perspective of their failure, their most fundamental weaknesses. With this objective in mind, I start with a succinct description of the decentralizing process in Argentina and the advantages that, according to its supporters, these actions would bring about. Afterwards, I criticize these concepts, detailing, according to the authors, the reasons why the expected results could not be achieved.
Keywords: Decentralization; provinces; municipalities; federalism; local development; structural adjustment